Equality Before the Law Against Police Officers Perpetrating Violence Against Children in the Tual Incident - Breavento Rahma Yudha; Subadi; Meirza Aulia Chairani (Cv. Kayaswara, Indonesia, 2026)
Purpose of the study: This study analyses the implementation of equality before the law toward police officers who committed violence against children in the Tual incident and formulates the ideal model of criminal liability for such officers. Methodology: The study employs normative legal research using statutory and conceptual approaches, examining the 1945 Constitution, Law No. 1 of 2023 on the Criminal Code, Law No. 2 of 2002 on the Indonesian National Police, Law No. 35 of 2014 on Child Protection, and Law No. 39 of 1999 on Human Rights, analysed descriptively and qualitatively. Main Findings: Equality before the law has not been optimally realised, owing to entrenched esprit de corps, weak internal and external oversight, conflicts of interest arising from institutional self-investigation, and asymmetric power relations within the law-enforcement system. Ideal criminal liability must be independent, transparent, and accountable. Novelty/Originality of this study: This study situates equality before the law at the intersection of child protection, human rights, and the criminal accountability of state officials. It advances existing knowledge by offering a concrete model of liability that integrates criminal and ethical sanctions, independent external oversight, and institutional reform oriented toward the best interests of the child, addressing persistent preferential treatment in Indonesian law-enforcement practice